Household modifications after the indoor residual spraying (IRS) campaign in Mozambique reduce the actual spray coverage and efficacy. - Mercy Opiyo; Ellie Sherrard-Smith; Arlindo Malheia; Arsenio Nhacolo; Charfudin Sacoor; Ariel Nhacolo; Mara Máquina; Luis Jamu; Nelson Cuamba; Quique Bassat; Francisco Saúte; Krijn Paaijmans (Public Library of Science (PLoS), 2022)
Indoor residual spraying of insecticides (IRS) is a key malaria vector control strategy. Whilst human attitude towards IRS is monitored before or shortly after implementation, human activities leading to the modification of insecticide-treated walls post-IRS are not. This could inadvertently reduce the protective effects of IRS. We monitored the extent of modifications to the sprayed indoor wall surfaces by household owners for six months post-IRS campaigns in two districts targeted for malaria elimination in southern Mozambique. In parallel, we assessed building of any additional rooms onto compounds, and mosquito net use. We quantified the contribution of wall modifications, added rooms, prolonged spray campaigns, and product residual efficacies on actual IRS coverage and relative mosquito bite reduction, using a mechanistic approach. Household owners continually modified insecticide-treated walls and added rooms onto compounds. Household surveys in southern Mozambique showed frequent modification of indoor walls (0-17.2% of households modified rooms monthly) and/or added rooms (0-16.2% of households added rooms monthly). Actual IRS coverage reduced from an assumed 97% to just 39% in Matutuine, but only from 96% to 91% in Boane, translating to 43% and 5.8% estimated increases in relative daily mosquito bites per person. Integrating post-IRS knowledge, attitude, and practice (KAP) surveys into programmatic evaluations to capture these modification and construction trends can help improve IRS program efficiency and product assessment.